Dissemination of technology utilization of FM community radio as a means to support teaching learning activities for students during the covid-19 pandemic at Muhammadiyah Elementary School Tlogolelo, Hargomulyo Village, Yogyakarta Special Region, Indonesi - Widyasmoro Widyasmoro; Iswanto Suwarno; Indar Surahmat; Toha Ardi Nugraha; Israa Al_barazanchi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Schools have used an online learning system during the COVID-19 pandemic. However, several schools are still not covered by cellular services due to their remote locations. The community service activity aimed to provide alternative solutions and support for the online learning and teaching activities at Muhammadiyah elementary school in Tlogolelo, Hargomulyo village, located in Yogyakarta Special Region, Indonesia. The main issue was that not all students could participate in online learning because of poor cellular signals in the area, which hampered internet access. Furthermore, some students had limited resources to support infrastructure for online learning, namely because they did not have smartphones or had to take turns with their siblings or parents. The main program implemented was the procurement and installation of supporting facilities to utilize and optimize the existence of Radio Voice Education. The community service team provided several radio receivers, including FM radios for underprivileged students and Android smartphone devices to assist teachers in creating radio-based learning content. Several activities to increase teacher capacity in creating educational content based on FM community radio were also included in this program, such as socialization and training on the use of Android-based podcast applications, Anchor FM, and Spotify, as well as assistance in making FM community radio-based learning- content.